2017
DOI: 10.1007/s40261-017-0497-0
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interaction Potential of Osilodrostat (LCI699) Based on Its Effect on the Pharmacokinetics of Probe Drugs of Cytochrome P450 Enzymes in Healthy Adults

Abstract: Background and ObjectivesOsilodrostat (LCI699) is an adrenal steroidogenesis inhibitor currently in late-phase clinical development as a potential treatment for Cushing’s disease. This study evaluated the inhibitory effect of osilodrostat on the pharmacokinetics of probe substrates of the cytochrome P450 (CYP) enzymes CYP1A2, CYP2C19, CYP2D6, and CYP3A4.MethodsHealthy adult volunteers received single-dose cocktail probe substrates [caffeine (100 mg), omeprazole (20 mg), dextromethorphan (30 mg), and midazolam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
(26 reference statements)
3
13
0
1
Order By: Relevance
“…Dextromethorphan plasma AUC ratio and dextromethorphan-to-dextrorphan molar urinary ratio are both often used as markers for CYP2D6 activity in drug interaction studies. 20,21,23,32,33 The dextromethorphan-to-dextrorphan molar urinary ratio was the suggested CYP2D6 activity marker for the Cooperstown 5+1 cocktail. 20 In the current study, the results were consistent between the 2 measures, but slightly more variable for dextromethorphanto-dextrorphan molar urinary ratio than for dextromethorphan plasma AUC ratio (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Dextromethorphan plasma AUC ratio and dextromethorphan-to-dextrorphan molar urinary ratio are both often used as markers for CYP2D6 activity in drug interaction studies. 20,21,23,32,33 The dextromethorphan-to-dextrorphan molar urinary ratio was the suggested CYP2D6 activity marker for the Cooperstown 5+1 cocktail. 20 In the current study, the results were consistent between the 2 measures, but slightly more variable for dextromethorphanto-dextrorphan molar urinary ratio than for dextromethorphan plasma AUC ratio (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A cocktail approach, involving simultaneous administration of substrates for multiple CYP isozymes to subjects, is effective for evaluation of whether a test drug has the potential for clinically significant DDIs with multiple enzymes. Many cocktail combinations have been reported and their usefulness for DDI evaluation has been proven . However, the use of repaglinide in a cocktail as a substrate for CYP2C8 and the combination of substrates used in this study for several CYP isozymes (CYP1A2, CYP2B6, CYP2C8, CYP2C9, and CYP3A) has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The key question to introspect: would lack of applying specific ADME screens for NASH in adjudicating a drug for clinical development lead to either low/moderate response or therapeutic failure during clinical trials in relevant NASH patients? This question has been asked after rosuvastatin showed poor response in NASH (55). It was reasoned that due to altered transporter related disposition in NASH, the uptake of rosuvastatin into the liver may have been reduced with the concomitant faster basolateral efflux facilitating excretory mechanisms including biliary clearance as qualitatively suggested in the schematic represented in Figure 1 (59-61).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we also suggest evaluation whether or not the drug is a perpetrator in NASH patients, using the cocktail approach for CYP enzymes/transporters. Recent literature has provided the impetus for planning and execution of such cocktail probe studies in NASH patients (55)(56)(57).…”
Section: Clinical Pharmacology Strategymentioning
confidence: 99%